Projects Based Learning Model to Increase Results and Student Activities - Mesterjon; Suwarni; Diah Selviani (Technium Social Sciences Journal, 2020)
The implementation of this research is Classroom Action Research (CAR). The data of SMKS 4 PGRI Bengkulu city. students from 14 students were only 5 students (36%) who had received Good grades, while 9 students (64%) needed guidance or had not reached KKM and based on the above background, the research problem can be formulated, namely how to apply the Project Based Learning model to improve student learning outcomes. The Method was conducted in two cycles with the flow of research, namely: action plan, implementation of action, observation and reflection. The results of the research that have been carried out can be concluded that the application of the Project Based Learning model can improve the quality of student learning process activities, by giving projects to students, providing feedback to students and motivating students. Learning models based on Project Based Learning can also improve the quality of student learning outcomes and activities. In each cycle there is an increase, this is seen from the results of the analysis of the cycle I test until the second cycle. Student learning outcomes, namely for the first cycle the average value of students is 71.66 with classical learning completeness 83.33%, increasing in the second cycle with an average value of 80.42 with 100% classical learning completeness. This research had a weakness which is the students had not ability to their kognitif aspect because to lowest the teacher was not creativity to leraning process in the classrooom.